Peripheral, head and neck surgery - Coventry, Brendon J. (Surgery: Complications, Risks and Consequences, 2014)
Written by internationally acclaimed specialists, Peripheral, Head and Neck Surgery expands on surgical procedures for the neck, head, hands and feet. Chapters provide pertinent and concise procedure descriptions creating a book that is both comprehensive and accessible. Stages of operative approaches with relevant technical considerations are outlined in an easily understandable manner. Complications are reviewed when appropriate for the organ system and problem. The text is illustrated throughout by photographs that depict anatomic or technical principles. Forming part of the series, Surgery: Complications, Risks and Consequences, this volume Peripheral, Head and Neck Surgery provides a valuable resource for all general surgeons and residents in training. Other healthcare providers will also find this a useful resource.